Trailer Wrap: Re-Fabricating Manufactured Housing - Michael Hughes; Bruce Wrightsman (Oz, 2006)
TrailerWrap is an innovative, community design/build project focused on engaging students in issues of sustainable and affordable design in the context of the trailer park. At the scale of an individual building the project explores the potential for providing affordable housing through the adaptive reuse and recycling of old, inefficient mobile homes.